Licensing of Chlorine Gas Infusion Applicators in Florida - Frederick M. Fishel (EDIS, 2007)
PI-153, a 3-page fact sheet by Frederick M. Fishel, explains the licensing and regulation of persons who use a portable infusion system to treat water with chlorine gas in Florida. Published by the UF Pesticide Information Office, June 2007 and reprinted December 2019.